Effects of environmental pH and ionic strength on the physical stability of cinnamaldehyde-loaded liposomes. Issue 10 (3rd August 2020) - Wang, Xuejiao; Swing, Caleb John; Feng, Tingting; Xia, Shuqin; Yu, Jingyang; Zhang, Xiaoming
Abstract: The physical stability of cinnamaldehyde-loaded liposomes was investigated under various conditions including different storage time, storage temperature, pH and ionic strength of external environment, as well as variations in hydration media. Results showed that the average diameter of liposomes increased first and remained constant, the retention rate (RR) decreased while the liposomes stored at higher temperature exhibited a lower RR during the storage period of 9 days. Furthermore, liposomes under acidic conditions (pH ≤ 6) exhibited a decreased particle size with an increased RR. As for the ionic strength of the external environment and hydration media, the particle size of liposomes increased, whereas the RR and encapsulation efficiency (EE) decreased as ionic strength increased. Atomic force microscopy (AFM) further proved that high ionic strength could result in instability of liposomes. However, the particle size of liposomes in the external environment composed of ion solution were far more than those in the hydration media, which indicated that the liposomes prepared in ion solution could resist instability caused by changes in external ionic strength. These results also provided a guidance for the application of liposomes in different environments and selectively preparing desired liposomes by modulating the pH and ionic strength of environment. Graphical Abstract: uf0001